2002
DOI: 10.1006/jdeq.2001.4064
|View full text |Cite
|
Sign up to set email alerts
|

Linear Estimation of the Number of Zeros of Abelian Integrals for Some Cubic Isochronous Centers

Abstract: This paper consists of two parts. In the first part we study the relationship between conic centers (all orbits near a singular point of center type are conics) and isochronous centers of polynomial systems. In the second part we study the number of limit cycles that bifurcate from the periodic orbits of cubic reversible isochronous centers having all their orbits formed by conics, when we perturb such systems inside the class of all polynomial systems of degree n. © 2002 Elsevier Science (USA)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…With the help of numerical analysis (using Maple or Mathematica) we showed that there exist parameter groups such that at least 15 to 24 limit cycles exist, having the configurations of compound eyes in these systems. The cases for q = 2 and 3 are being reported separately in [Chan et al, 2001] and [Li et al, 2002] where at least 15 and 23 limit cycles are respectively obtained. The case for q = 6 is discussed in [Li et al, 2002].…”
Section: Global and Local Bifurcations Of Z Q -Equivariant Vector Fieldsmentioning
confidence: 99%
“…With the help of numerical analysis (using Maple or Mathematica) we showed that there exist parameter groups such that at least 15 to 24 limit cycles exist, having the configurations of compound eyes in these systems. The cases for q = 2 and 3 are being reported separately in [Chan et al, 2001] and [Li et al, 2002] where at least 15 and 23 limit cycles are respectively obtained. The case for q = 6 is discussed in [Li et al, 2002].…”
Section: Global and Local Bifurcations Of Z Q -Equivariant Vector Fieldsmentioning
confidence: 99%
“…Thus, we get the systemẋ = 2y(x + α) 2 , y = −2(x + α)(αx − y 2 ), with α ̸ = 0. In [12] the authors studied the cubic polynomial differential systems having a rational first integral of degree 2 whose phase portraits correspond to the phase portraits P 1 , P 3 and P 4 of Figure 1. These systems were denoted in [12] by (A), (B) and (C).…”
Section: Introduction and Statement Of The Main Resultsmentioning
confidence: 99%
“…In [12] the authors studied the cubic polynomial differential systems having a rational first integral of degree 2 whose phase portraits correspond to the phase portraits P 1 , P 3 and P 4 of Figure 1. These systems were denoted in [12] by (A), (B) and (C). They also proved that all the centers of these systems are reversible and isochronous, see [12, p. 314].…”
Section: Introduction and Statement Of The Main Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper we shall perturb isochronous centers. The perturbation of some of these centers have already been studied see for instance [7,14]. For a survey on isochronous centers see [6].…”
Section: Introduction and Statement Of The Main Resultsmentioning
confidence: 99%